2007
DOI: 10.1111/j.1600-0501.2006.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing in critical‐size defects treated with bioactive glass/calcium sulfate: a histologic and histometric study in rat calvaria

Abstract: BG particles, used with or without a CS barrier, maintained the volume and contour of the area grafted in CSD. However, they did not lead to a significant difference in bone formation when compared with control at 12 weeks post-operative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 23 publications
7
51
2
7
Order By: Relevance
“…This demonstrated that 5-mm calvarial defect was of a critical size (non healing within the length of the study). This is in line with the results of several previous studies [20][21][22][23]. The bone healing in the test groups was found to be significantly higher than the bone healing achieved by the empty defect group (P<0.0001).…”
Section: Discussionsupporting
confidence: 82%
“…This demonstrated that 5-mm calvarial defect was of a critical size (non healing within the length of the study). This is in line with the results of several previous studies [20][21][22][23]. The bone healing in the test groups was found to be significantly higher than the bone healing achieved by the empty defect group (P<0.0001).…”
Section: Discussionsupporting
confidence: 82%
“…All cell-seeded scaffolds were maintained in a humidified incubator, at 37C and 5% CO 2, with medium changes every 3 days for 21 days prior implantation. According to previous studies, 5 mm calvarial defect is considered a critical-sized, non-healing defect along the length of the study [21,22].…”
Section: Tablementioning
confidence: 99%
“…Despite the good results obtained using SIS, few studies have evaluated the SIS sponge as a scaffold for repairing shaped bones. Several groups reported that stem cells or cytokines treated scaffolds exhibited complete healing of 5 mm bone defect of rat crania by as early as 4 weeks [36][37][38][39][40][41]. Accordingly, we used a surgical bone-defect model (5 mm) to easily assess the potential of the SIS sponge to act as a scaffold in the repair of damaged bone.…”
Section: Discussionmentioning
confidence: 99%